EXPERIMENTAL STUDY ON STEEL AND POLYPROPYLENE FIBERS MORTAR BOND STRENGTH UNDER UNIAXIAL TENSION - Djayaprabha, Herry Suryadi; Perceka, Wisena; Oriana, Angie (Applied Research on Civil Engineering and Environment (ARCEE), 2024)
The present study aims to investigate the bond behavior between fibers and mortar matrix in fiber-reinforced concrete, which was explored through a uniaxial tension test. The bond behavior was studied for different types of embedded fibers: steel fibers, polypropylene fibers, and hybridizations of steel and polypropylene fibers. The mixture proportion was determined based on the absolute volume method with a water-to-binder ratio (w/b) of 0.29 to achieve high-strength mortar. The high-strength mortar was cast by utilizing an industrial waste by-product of both silica fume and fly ash as a partial cement replacement. The compressive strength and uniaxial tension tests on high-strength mortar were conducted at the ages of 28 and 140 days. The long-term bond-strength behavior was investigated at the age of 140 days. The results showed that the average compressive strengths of hardened mortar on 28 and 140 days were 54.82 MPa and 69.37 MPa, respectively. Whereas, the average fiber-mortar bond strengths with steel, polypropylene, and hybridized fibers were 8.62 MPa, 8.37 MPa, and 7.30 MPa, respectively, at 28 days and 11.22 MPa, 10.21 MPa, and 11.82 MPa, respectively, at 140 days. Compared to the equivalent bond strength of the steel fiber, the polypropylene fiber had an equivalent bond strength of 2.90% and 9.00% lower at the ages of 28 and 140 days. Meanwhile, the equivalent bond strength of hybridized fiber was 15.31% lower than that of steel fiber; however, the long-term behavior of the hybridized fiber showed its performance was about 5,35% higher than that of steel fiber at 140 days.